Negative pressure wound therapy for surgical wounds healing by primary closure - Norman, G; Goh, EL; Dumville, JC; Shi, C; Liu, Z; Chiverton, L; Stankiewicz, M; Reid, A (Cochrane Collaboration, 2020)
Background: Indications for the use of negative pressure wound therapy (NPWT) are broad and include prophylaxis for surgical site infections (SSIs). Existing evidence for the effectiveness of NPWT on postoperative wounds healing by primary closure remains uncertain.